2019
DOI: 10.1096/fj.201900866rr
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia‐induced Netrin‐4 promotes neovascularization through endothelial progenitor cell activation via Unc‐5 Netrin receptor B

Abstract: Endothelial progenitor cells (EPCs) promote neovascularization and tissue repair by migrating to vascular injury sites; therefore, factors that enhance EPC homing to damaged tissues are of interest. Here, we provide evidence of the prominent role of the Netrin‐4 (NTN4)–Unc‐5 Netrin receptor B (UNC5B) axis in EPC‐specific promotion of ischemic neovascularization. Our results showed that NTN4 promoted the proliferation, chemotactic migration, and paracrine effects of small EPCs (SEPCs) and significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
(252 reference statements)
0
3
0
Order By: Relevance
“…For instance, it has been shown that NTN4 accelerates wound healing and decreases inflammation in the cornea [ 11 ]. On the contrary, the absence of NTN4 modulates pathological angiogenesis in the ischemic retina [ 6 , 9 , 12 ] and alters vascular architecture and immune cell turnover in the adult mouse retina [ 13 ]. However, these studies are limited to a few models and do not always reflect human pathology.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that NTN4 accelerates wound healing and decreases inflammation in the cornea [ 11 ]. On the contrary, the absence of NTN4 modulates pathological angiogenesis in the ischemic retina [ 6 , 9 , 12 ] and alters vascular architecture and immune cell turnover in the adult mouse retina [ 13 ]. However, these studies are limited to a few models and do not always reflect human pathology.…”
Section: Introductionmentioning
confidence: 99%
“…A high concentration of Ntn-4 (5 µg/ml) has been found to inhibit endothelial cell proliferation and promote endothelial cell apoptosis, whereas a low concentration of Ntn-4 (100 ng/ml) exerts the opposite effect ( 31 ). The majority of previously published studies have suggested that Ntn-4 binds to the receptor, Unc5B, to promote both the proliferation and differentiation of endothelial progenitor cells and the angiogenesis of ischaemic hind limbs in mice ( 32 ), whereas the proliferation and angiogenesis of human placental endothelial cells and retinas is inhibited ( 10 , 33 , 34 ). By contrast, it has been demonstrated that the role of Ntn-4 is mediated by regulating the BM through its interaction with laminin, rather than by binding to receptors of the Ntn family ( 13 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The wound healing process in chronic pressure ulcers is complicated, involving remodeling and deposition of extracellular matrix (ECM), cell proliferation, inflammation, and angiogenesis [ 3 , 4 ]. Meanwhile, endothelial progenitor cells (EPCs), which originated from the bone marrow upon acute injury, participate in the neovascularization [ 5 ]. The fluid EPCs numbers are applied as a marker of endothelial disorder or remedy several diseases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%